Implementation Dilemmas of - Malgas, Johannes (My University, 2011)
This research report examines institutional change in South Africa, with particular attention to the vexed issue of border management. Border control in South Africa is the responsibility of a range of government departments and agencies with unique and often overlapping mandates. The status of lead agency in border control has vacillated between main border control agencies over the years. Leadership has been handed from the South African Police Service to the Department of Home Affairs and, in February 2007, to the South African Revenue Service. The lead agent has always been at the mercy of voluntary cooperation from the other departments and agencies responsible for border control. It does not have statutory powers to enforce cooperation, resulting in individual border control departments and agencies retreating to narrow mandates to avoid “interference” from “outside”. Due to strong principal-agent relationships among political and bureaucratic elites as a result of the ruling party’s cadre deployment strategy, very little real change has been achieved during the last sixteen years. The current stalemate will only be broken through strong leadership at the top. A scan of the various models for integrated border control shows a great diversity in approaches. Consistent with all transformation of border management, is the attempt to make a clean break with the inefficiency and ineffectiveness of a proliferation of agencies or departments responsible for border control. Government must decide on the type of model it intends to follow to transform border control. Critically, a change in legislation to enable the required institutional change might very well be the first step out of this impasse
MM - P&DM
Keywords: Integrated border management; Border management, South Africa